Molecular Characterization of Dengue Virus Type 1 in Zhejiang in 2019 - Yao, Wenwu; Yang, Zhangnv; Lou, Xiuyu; Mao, Haiyan; Yan, Hao; Zhang, Yanjun (Frontiers in Cellular and Infection Microbiology, 2021)
Dengue fever (DF), caused by dengue virus (DENV), is a mosquito-borne viral disease and the most important arbovirus in the world. This study aimed to determine the molecular, epidemiological and phylogenetic characterization of 174 DENV - 1(132 indigenous cases and 42 imported cases) isolated from nine municipal of Zhejiang provinces in 2019. The analyses of phylogenetics, Haplotype and amino acid substitution were conducted based on the full envelope (E) gene sequences. 64 haplotypes were clustered into two main clades, isolates from Wenzhou and Taizhou mainly clustered into Clade I and Clade II mainly composed of Hangzhou and Ningbo cases. 6 sites of Amino acid substitutions including A88T, F96L, M297V, T339S, I378L and V436I were only observed in strains isolated from Ningbo and Hangzhou, while 2 sites of Amino acid substitutions including V312L and V380I were observed in strains from in Taizhou and Wenzhou. In our study, strains were high homology with the strains from Southeast Asian countries, cases in Zhejiang probably imported from Southeast Asian countries. The strains from different regions in Zhejiang were clustered in the same branch may be caused by the continuous import of cases in the same country at different time periods. After the continuous outbreak in Zhejiang Province, some sites of the dengue gene have been mutated, and the effects need further study.